Penggunaan Canva pada Pembelajaran Berbasis Proyek untuk Meningkatkan Keterampilan dan Motivasi Menulis Siswa - Siswanjaya Siswanjaya (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
Motivation and writing skill become interesting issue to know by all teachers. One of the writing assignments for eighth graders is writing greeting card. This study was aimed to examine whether the implementing of project-based learning and the use of Canva can improve students’ motivation and writing skills. The subject of this Classroom Action Research (CAR) was 30 students of class VIIIE of SMPN I Terbanggi Besar in the academic year 2019/2020 consisting 10 males and 20 females. Data collecting techniques were conducted by giving questionnaire to know the students’ motivation and writing project to know the students’ writing skill. This study conducted in two cycles. The finding of cycle I and cycle II show that the students’ score for motivation and writing aspects was increase. The mean score for the the student’s motivation was 59,9 in preliminary study, 74,1 in cycle I and 84,9 in cycle II. The mean score for students’ writing was 56,7 in preliminary study, 69,3 in cycle I and 79,6 in cycle II. It can be concluded that the implementing of project-based learning and the use of Canva can improve students’ motivation and writing skill.